2022
DOI: 10.17648/acta.scientiae.7019
|View full text |Cite
|
Sign up to set email alerts
|

Professional Learning of Physics Teachers in Lesson Study: Exploring Inquiry Tasks

Abstract: Background: Research concerning teachers’ professional learning in lesson study has been highlighted in Physics teaching; however, studies that examine this process from the elaboration of inquiry tasks are still scarce. This kind of task makes it possible to explore physical concepts and relationships due to their open nature, which contemplates the students’ interest, involves a practical dimension, and promotes successful learning situations. Objectives: To understand Physics teachers’ professional learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Thus, the structure and dynamics of the research lesson on Ohm's law were constituted in a context to promote the learning of that topic (Baptista et al, 2020;Tomkelski et al, 2022) insofar as they favored the exploration of MRs and revealed their contributions to the learning of this concept, in addition to favoring new professional experiences throughout teachers' careers, contributing to their training process (Ribeiro & Ponte, 2019;. It also provided moments of interaction between the teachers that made possible the confrontation and the necessary modifications to the reinterpretation of their experiences (Flores, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the structure and dynamics of the research lesson on Ohm's law were constituted in a context to promote the learning of that topic (Baptista et al, 2020;Tomkelski et al, 2022) insofar as they favored the exploration of MRs and revealed their contributions to the learning of this concept, in addition to favoring new professional experiences throughout teachers' careers, contributing to their training process (Ribeiro & Ponte, 2019;. It also provided moments of interaction between the teachers that made possible the confrontation and the necessary modifications to the reinterpretation of their experiences (Flores, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into lesson study as a formative process for physics teachers have shown promising results (for example, Baptista et al, 2020;Juhler, 2018;Tomkelski et al, 2022;Zhou et al, 2016), but there are still few investigations in lesson studies with teachers in the areas of the natural sciences, especially on the use of MRs in physics teaching (for example, Baptista et al, 2020;Conceição et al, 2021). In addition, much of the research on lesson studies involves initial teacher education in mathematics, and fewer studies address physics (for example, Conceição et al, 2016;Pektas, 2014;Rodrigues & Arroio, 2020).…”
Section: Introductionmentioning
confidence: 99%